DEPICTION OF HUMAN TRAGEDY IN “NICHOLAS NICKELBY” BY CHARLES DICKENS (SCIENCE TIME JOURNAL, 2023)
In this article, the analysis of human tragedy and problems in “Nicholas Nickelby” by Charles Dickens has been discussed and analysed with the help of some examples.